Hubungan antara Sikap Santun dan Gotong Royong terhadap Hasil Belajar Siswa pada Pelajaran PKN - Dewi Asri Fatma Sari; Titania Galuh Ramadani; Siti Lailiyah (Madrasah Ibtidaiyah Education Journal, 2025)
This study aims to determine the relationship between politeness and cooperation on the learning outcomes of Civic Education (PPKn) in fourth-grade students of MI Mambaul Ulum Kedungkampil. The research approach used is a quantitative approach with a correlational method. The population in this study was all fourth-grade students, with a sample of 52 respondents taken randomly. Data were obtained through a questionnaire on politeness and mutual cooperation attitudes, as well as documentation of Civic Education learning outcomes. The results of data analysis using the Pearson correlation test showed that there was a positive and significant relationship between politeness and learning outcomes (r = 0.288; p = 0.039 < 0.05) and between cooperation attitudes and learning outcomes (r = 0.302; p = 0.030 < 0.05). In addition, there was also a significant relationship between politeness and cooperation attitudes (r = 0.331; p = 0.017 < 0.05). The strength of the relationship between the variables is classified as moderate, indicating that the higher the students' politeness and cooperation, the better their civics learning outcomes. Thus, positive social values ​​such as politeness and cooperation play a significant role in supporting student learning success in elementary schools.